The news text (10) (Journal of Parents and Teachers, 2025)
The article refers to news texts, which should be clear, easily understandable, and of great interest. Additionally, the article outlines the editing guidelines for journalistic texts and discusses the text as context, taking into account what constitutes a news story and the context of each day.
Keywords: newspaper; read; texts; guidelines; comprehension